A forma do informe: uma interpretação da morfogênese do território metropolitano da grande Vitória a partir dos padrões e processos de antropização - Borges, Heraldo Ferreira (2018)
We live in an urban world. However, this "urban" does not necessarily mean cities, or at least not cities as physical entities clearly limited and differentiated from the surrounding landscape, as it existed until the beginning of the 20th century. Mostly we live in areas, agglomerations or urban regions, scattered and dispersed occupations along great extensions of territory, forming a continuous urban landscape. Contrary to the common sense that these urban continuums are amorphous, this research has as main motivation to contradict this assumption by exploring and identifying its form, that is, what is the form of the inform? The complexity and heterogeneity of the causes of this reality enable different and complementary approaches - from human geography, applied economics, sociology, among others - to their understanding. This work is specifically interested in the morphological and morphogenic approximation of nowadays metropolitan territories. This means that it is an approximation that places emphasis on the morphological dimension of constructed reality, as a complementary explanation, but differentiated from those more economistic or sociological approaches of character. The main objective of this thesis is to understand the morphological formation of contemporary metropolitan territories by identifying, in time and space, the patterns and processes of anthropization through an interpretative and diacronic cartographic reading. These patterns and processes are analyzed on two scales: the scale of the totality, or regional metropolitan, more comprehensive and not restricted to the politicaladministrative limit of the RMGV, when analyzing the most representative element, the route (from its axis); and on the scale of the fragment, or of the more detailed urban fabric covering the elements constituting the fabric: building, lot, street and uses.